FRI0219 Association between conversion to ACPA/RF seronegative status and clinical outcomes following treatment with abatacept in combination with methotrexate compared with methotrexate alone in patients with early rheumatoid arthritis and poor prognostic indicators. (15th June 2017) - Jansen, D; Emery, P; Smolen, J; Westhovens, R; Bars, M Le; Connolly, S; Ye, J; Toes, R; Huizinga, T
Abstract : Background: RA is characterized by the production of autoantibodies, including anti-citrullinated protein antibodies (ACPA) and RF, which are associated with poor prognosis in RA. 1–3 More data on the clinical significance of ACPA/RF seroconversion in response to treatment are needed. Evidence suggests a role for T cells in ACPA production. 2, 3 Objectives: This post hoc analysis investigated the effect of the T-cell co-stimulation modulator abatacept (ABA) in combination with MTX vs MTX alone on conversion of ACPA positive (+) and RF+ patients (pts) to seronegative status, and the relationship between conversion to seronegative status and clinical response. Methods: Data from a double-blind, randomized, Phase III study (AGREE; NCT00122382 ) conducted in MTX-naïve pts with early RA (≤2 years) and poor prognostic factors (ACPA+ and/or RF+ with evidence of erosions) were included. 4 Pts were randomized to ABA (∼10 mg/kg IV according to weight)+MTX or placebo+MTX (MTX alone) in a 12-month (M) double-blind phase followed by 12M of open-label ABA+MTX. Autoantibody titres were assessed at baseline and 6M and 12M of the double-blind phase by ELISA. Pts with titres below the threshold for positivity (ACPA 5 AU/mL; RF [IgM] 15 IU/mL) at M6 or M12 were considered to have converted to seronegative status. The relationship between conversion to ACPA seronegative status and clinical response at M6 and M12 was determined. All analyses were descriptive and based on pts with available DAS28 (CRP) and CDAI data at baseline and M6 and M12. Results: A total of 435 and 461 pts, respectively, were ACPA+ or RF+ at baseline and had known serostatus at M6 and M12. At 6M, 6.6% (15/227) and 17.0% (39/230) of ABA+MTX pts were ACPA and RF negative, respectively, vs 2.9% (6/208) and 9.5% (22/231) of MTX pts. At 12M, 7.1% (15/212) and 18.5% (41/222) of ABA + MTX pts were ACPA and RF negative, respectively, vs 4.5% (9/198) and 14.6% (32/219) of MTX pts. A higher proportion of pts receiving ABA + MTX who converted to ACPA seronegative status achieved remission (DAS28 [CRP] <2.6 or CDAI ≤2.8) compared with ABA + MTX-treated pts who remained ACPA+ or with pts treated with MTX alone regardless of whether they converted to seronegative status or not (Figure). Pts receiving ABA + MTX who converted to ACPA seronegative status also had a numerically higher cumulative probability of achieving sustained remission (DAS28 [CRP] <2.6) and lower radiographic progression than pts receiving MTX who converted to seronegative status or pts in either treatment group who remained ACPA+ (data not shown). Conclusions: Compared with MTX alone, treatment with abatacept + MTX was more likely to result in conversion to ACPA/RF seronegative status in pts with early erosive RA. Conversion to ACPA seronegative status was associated with better clinical and radiographic outcomes. References: Scott DL, et al. Lancet 2010;376:1094–108. Hecht C, et al. Ann Rheum Dis 2015;74:2151–6. Aletaha D, et al. Arthritis Res Ther 2015;17:229. Rombouts Y, et al. Ann Rheum Dis 2016;75:578–85. Disclosure of Interest: D. Jansen: None declared, P. Emery Grant/research support from: AbbVie, Merck, Pfizer, Roche, Consultant for: AbbVie, Bristol-Myers Squibb, Merck, Pfizer, Roche, Lilly, Novartis, Samsung Bioepis, J. Smolen Grant/research support from: AbbVie, Janssen, Lilly, MSD, Pfizer, Roche, Consultant for: AbbVie, Amgen, AstraZeneca, Astro, Bristol-Myers Squibb, Celgene, Celltrion, Chugai, Gilead, GSK, ILTOO, Janssen, Lilly, MedImmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi, UCB, R. Westhovens Grant/research support from: Roche, Consultant for: Janssen, Celltrion, Galapagos, Speakers bureau: Bristol-Myers Squibb, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. Ye Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, R. Toes: None declared, T. Huizinga Grant/research support from: EU & Dutch Arthritis Foundation, Consultant for: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Crescendo Bioscience, Inc, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough, UCB, Inc., Eli Lilly, Speakers bureau: Abbott Laboratories, Biotest AG, Bristol-Myers Squibb, Novartis Pharmaceuticals Corporation, Pfizer Inc, Roche, sanofi-aventis, Schering-Plough